MANAGEMENT PROCEDURE OF T-TUBE CHOLANGIOGRAPHY EXAMINATION IN POSTOPERATIVE T-TUBE PATIENTS AT THE RADIOLOGY DEPARTMENT OF ARIFIN ACHMAD REGIONAL GENERAL HOSPITAL - Muhammad Wildan; Ghea Aprilia; Khanza suryani; Desviyanti serli (LPPM Universitas Awal Bros, 2026)
Background: T-tube cholangiography is a radiographic examination of the biliary system using contrast media administered through a T-tube catheter to evaluate the bile ducts, assess the smooth passage of contrast media, and detect obstruction or abnormalities of the biliary system. In clinical practice, examination procedures may differ from theoretical guidelines, particularly in terms of patient preparation and projection selection. Objective: This study aimed to determine the procedure for performing cholangiography examinations in patients with a postoperative T-tube clinical condition at the Radiology Department of Arifin Achmad Regional General Hospital, Riau Province. Methods: This study employed a descriptive qualitative method with a case study approach. Data were collected through direct observation, interviews, documentation, and evaluation of radiographic findings from examinations performed at the Radiology Department of Arifin Achmad Regional General Hospital between June and July 2024. Results: The cholangiography examination procedure in patients with a postoperative T-tube clinical condition did not require special preparation and was performed using preliminary Anteroposterior (AP) and post-contrast AP projections. Contrast media were carefully administered through the T-tube catheter until the duodenum was reached. The radiological report showed contrast filling of the right and left hepatic ducts, common hepatic duct, and common bile duct, with smooth passage into the duodenum. No filling defects or additional shadows were identified. Right Posterior Oblique (RPO) and lateral projections were performed as additional projections when the AP images were insufficient to establish the diagnosis.